Iatrogenic perforation of a pulmonary artery side branch—a case report. Issue 6 (17th June 2021) - Leick, Juergen; Leinen, Stefan; Friedrich, Ivar; Werner, Nikos
Abstract: Background: The use of a pulmonary artery catheter (PAC) continues to be important for the diagnosis and therapeutic control of severe heart failure and in the diagnosis of pulmonary arterial hypertension. One of the most feared complications of this examination is perforation of a pulmonary artery with an estimated incidence of 0.031–0.05% and mortality rates of up to 70%. Case summary: We report on an 80-year-old female patient who experienced a perforation of a pulmonary artery branch during the work-up of pulmonary arterial hypertension by PAC. Immediately after the perforation, haemodynamic shock developed rapidly, necessitating cardiopulmonary resuscitation. Occlusion of the pulmonary artery branch with a semicompliant balloon was applied immediately. After 40 min of occlusion, the bleeding persisted, and endovascular coil implantation was performed. Subsequently, the bleeding stopped, and the haemodynamics stabilized. After treatment, the patient was discharged home without any significant sequelae. Discussion: Treatment options in pulmonary artery perforation are limited, especially if the patient is inoperable and if balloon occlusion fails. Based on our results, endovascular coil embolization can be considered a therapeutic option.